Comparative analysis of ethylene-induced ripening in climacteric and non-climacteric fruits: implications for post-harvest management - Dwi Arista, Nor Isnaeini; Ardiningtyas, Siti Azizah (Social Agriculture, Food System, and Environmental Sustainability, 2024)
Background: Ethylene gas contained in fruits can increase the respiration rate. Climacteric fruits are those that experience automatic stimulation towards ripening, accompanied by an increase in respiration rate, as seen in bananas. Non-climacteric fruits, such as oranges, do not experience such an increase or change in respiration rate. The rate of fruit ripening is influenced by temperature, storage conditions, and the use of chemical agents to accelerate ripening. The aim of this article is to investigate the effects of closed and open storage environments, as well as the concentration of chemical agents used in the storage process. Methods: This study used bananas and tomatoes, which were placed in both open and closed storage, and stored in pairs. Additionally, the article discusses the concentration of carbide as a chemical agent that triggers the ripening of oranges. Findings: The results show that bananas and tomatoes are climacteric fruits. The storage treatment of bananas indicated that, across all conditions—whether stored in open or closed environments, or stored together with tomatoes—the outcome was the same: the fruits showed signs of deterioration within one week. For tomatoes, it was observed that storing them in a closed environment led to greater longevity compared to other storage methods. The treatment of oranges showed that ripening occurred more rapidly with the application of carbide compared to without its use. Conclusion: Ethylene gas is a crucial factor in the post-harvest management of various fruits and vegetables. Inadequate handling can lead to mechanical damage. In practice, bananas produce the most ethylene gas compared to tomatoes and oranges. Furthermore, bananas can influence the ripening of surrounding fruits. The use of carbide in different concentrations demonstrated that 10 grams of carbide led to faster ripening and yellowing of oranges compared to lower concentrations or the absence of carbide. Novelty/Originality of this article: This study uniquely integrates the analysis of natural and chemically-induced ethylene effects on climacteric and non-climacteric fruits under varied storage conditions, providing novel insights for optimizing post-harvest management across diverse fruit types.